Audit Quality Perception: Beyond the 'Role‐Perception Gap'. Issue 2 (3rd May 2016) - Gonthier‐Besacier, Nathalie; Hottegindre, Géraldine; Fine‐Falcy, Sandrine
Abstract : This paper measures differences in the perception of audit quality between professionals, and attempts to categorise the professionals on the basis of their perceptions. We firstly perform a REBUS‐PLS analysis. We thus identify three groups of professionals with different audit quality perceptions. We then run chi‐square tests to evaluate differences in perception depending firstly on the professional's role in the audit process (auditor vs. preparer) and then by incorporating other variables connected with the individuals' own characteristics. Contrary to existing research, our study reveals no significant differences in perception between auditors and preparers. In contrast, our study indicates that differences in audit quality perception can be explained in particular by the professionals' level of expertise and the existence of shared values among professionals. This study therefore demonstrates the need to look beyond the 'role‐perception gap' in order to understand differences in audit quality perception. It confirms the existence of an 'epistemic community' that explains the differences in audit quality perception.